Knowledge and Prevention of Farmer Households to the Japanese Encephalitis Infection in Badung Regency, Bali Province, Indonesia - Ambarawati, I Gusti Agung Ayu; Adi, Anak Agung Ayu Mirah; Damayanti, Putu Ayu Asri; Kardena, I Made; Hongo, Chiharu (Advances in Social Sciences Research Journal, 2020)
It was reported that 326 Japanese Encephalitis (JE) cases in Indonesia in 2016, majority cases (69.3%) occurred in Bali. It shows that Bali is a prone-area to JE incidence. Previous studies noted that JE is closely related to rural and suburban areas where rice culture and pig farming coexist. This study aims at i) determining knowledge and preventive practices of JE by farmer households; (ii) observing types of mosquitos around farmer households; and (iii) mapping the potency of JE spread using geo-spatial information. Result from this research shows that farmer households have limited knowledge and preventive actions to the incidence of Japanese encephalitis. Preventive actions carried out by respondents were not for JE incidence as such. Nonetheless, farmer’s response to source of vectors and cleanliness are good preventive actions not just to JE incidence but also for other diseases. In this research, setting up mosquito’s light traps nearby pig pens and rice fields has been successful. The result shows that Culex tritaeniorhynchus was dominant type of mosquito trapped. This is an indication that the selected areas are susceptible to the incidence of JE as the Culex sp was reported as the most competent of JE vector in Asia. Maps of the JE spread in Badung regency also coincidence with the places of Culex sp trapped and the dense of rice field. Based on the limitation of knowledge and preventive actions carried out by farmer households, it is important for the stakeholders in the regency including Regional Health Office and health care workers to socialize the occurrence of JE in the community and how to prevent against the disease.